PENULISAN ARTIKEL (PTK) PENELITIAN TINDAKAN KELAS BAGI MAHASISWA PENDIDIKAN MATEMATIKA UIN SYAHADA PADANGSIDIMPUAN - Torang Siregar (CV. Alfa Pustaka, 2025)
The culture of writing is one of the key indicators in enhancing the professionalism of future educators, particularly students of mathematics education. One initial step to develop academic writing culture is through the writing of articles based on Classroom Action Research (CAR). CAR is highly suitable for students, as the research context is directly within the classroom, where various issues and learning dynamics occur. This type of research can stem from real problems affecting the teaching and learning process, such as teaching methods, media, teacher-student interaction, or student motivation. Through the CAR process, students not only learn how to conduct research, but also how to express their findings in scientific articles that can be published. Thus, writing articles based on CAR results serves not only as a means of self-development but also as a real contribution to the advancement of educational science and the improvement of learning quality. Furthermore, the articles written from such research can become valuable references for teachers, lecturers, or other researchers in solving similar problems in their classrooms. Therefore, students need to be equipped with the skills and motivation to write scientific articles early on, so that they can produce quality, useful, and educationally relevant written works.